Effectiveness of Team Quiz Method in Improving The Tajweed Learning and Student Activity at SDLB Putramanunggal Gombong - Budiono, Budiono (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
This study aims to determine the effectiveness of team quiz method to improve the tajweed learning and student activity on students with visual impairments in grade 4 at SDLB Putra Manunggal Gombong, Kebumen. This research is a classroom action research with 6 students as the research subjects. This study consisted of 2 cycles that each cycle has 2 times of meetings. The utilized instruments were test sheet, interview sheet, and observation sheet. Triangulation techniques was used to validate the data. The results showed that: 1) the team quiz method was effective in improving the tajweed learning and student activity that achieved a good category; 2) the tajweed learning was increased an average value in the first cycle by number 57,5 with 58,33% learning completeness whereas in the second cycle was 75 with 91,66% learning completeness; 3) the student activity was increased with an average score in the first cycle was 27 and in the second cycle was 35.